Characterization of Human Immunodeficiency Virus (HIV) Infections in Women Who Received Injectable Cabotegravir or Tenofovir Disoproxil Fumarate/Emtricitabine for HIV Prevention: HPTN 084. (18th March 2022) - Eshleman, Susan H; Fogel, Jessica M; Piwowar-Manning, Estelle; Chau, Gordon; Cummings, Vanessa; Agyei, Yaw; Richardson, Paul; Sullivan, Philip; Haines, Casey D; Bushman, Lane R; Petropoulos, Christos; Persaud, Deborah; et al.
Abstract: Background: HIV Prevention Trials Network 084 demonstrated that long-acting injectable cabotegravir (CAB) was superior to daily oral tenofovir (TFV) disoproxil fumarate (TDF)/emtricitabine (FTC) for preventing human immunodeficiency virus (HIV) infection in sub-Saharan African women. This report describes HIV infections that occurred in the trial before unblinding. Methods: Testing was performed using HIV diagnostic assays, viral load testing, a single-copy RNA assay, and HIV genotyping. Plasma CAB, plasma TFV, and intraerythrocytic TFV-diphosphate concentrations were determined by liquid chromatography–tandem mass spectrometry. Results: Forty HIV infections were identified (CAB arm, 1 baseline infection, 3 incident infections; TDF/FTC arm, 36 incident infections). The incident infections in the CAB arm included 2 with no recent drug exposure and no CAB injections and 1 with delayed injections; in 35 of 36 cases in the TDF/FTC arm, drug concentrations indicated low or no adherence. None of the cases had CAB resistance. Nine women in the TDF/FTC arm had nonnucleoside reverse-transcriptase inhibitor resistance; 1 had the nucleoside reverse-transcriptase inhibitor resistance mutation, M184V. Conclusions: Almost all incident HIV infections occurred in the setting of unquantifiable or low drug concentrations. CAB resistance was not detected. Transmitted nonnucleoside reverse-transcriptase inhibitor resistance was common; 1 woman may have acquired nucleoside reverse-transcriptase inhibitor resistance from study drug exposure. Abstract : Human immunodeficiency virus (HIV) infections were characterized in women receiving long-acting cabotegravir or oral tenofovir disoproxil fumarate/emtricitabine for HIV prevention. Almost all incident HIV infections occurred in the setting of unquantifiable or low drug concentrations. Cabotegravir resistance was not detected.